Исследование применения квадрокоптеров для игровой индустрии - Пругер, И. Н.; Хмелик, О. Г. (ХНУРЭ, 2019)
The purpose of this work is to study the use of quadrocopters for the gaming industry.
Keywords: gaming industry; quadrocopters